2013
DOI: 10.1093/eurpub/ckt117
|View full text |Cite
|
Sign up to set email alerts
|

Is exposure to night-time traffic noise a risk factor for purchase of anxiolytic–hypnotic medication? A cohort study

Abstract: We found some evidence that potential exposure to night-time road traffic noise might affect individual use of anxiolytics-hypnotics. Further research based on strictly individual approaches is warranted to assess exposure to road traffic noise more precisely and reliably than allowed by noise propagation prediction models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…2,[4][5][6][7]9 Similarly epidemiological studies have shown that noise exposure is associated with self-reported health, 56 depression, 56,57 cardiovascular disease, [58][59][60][61][62] and mortality. 62,63 These associations often persist after adjustment for classic behavioral and biomedical risk factors, suggesting that other factors may partly explain these associations.…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6][7]9 Similarly epidemiological studies have shown that noise exposure is associated with self-reported health, 56 depression, 56,57 cardiovascular disease, [58][59][60][61][62] and mortality. 62,63 These associations often persist after adjustment for classic behavioral and biomedical risk factors, suggesting that other factors may partly explain these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Traffic noise: self-rated health and medication use associations between road traffic noise (a more common environmental nuisance than aircraft noise) and self-rated health (8) or psychotropic medication use (eg, hypnotics) (17)(18)(19) among adults, and even fewer have studied how noise-sensitivity affects these associations (20).…”
mentioning
confidence: 99%
“…In summary, two studies with objective data on the individual level (11,16) and one study relying on self-reports (8) showed no overall associations between road traffic noise and antidepressants, anxiolytics or hypnotics. Three studies of aircraft noise showed positive associations between noise and medications, but, in two of the studies, data on medications were self-reported (4,10), and the one using objective data had an ecological design (14,15).…”
Section: Medication Use As An Outcome Variable In Environmental (Noismentioning
confidence: 87%
“…The only previous study using objective data on the individual level, studied the association between road traffic noise and use of anxiolytics or hypnotics in Marseille, France (16). Among 181 000 individuals, there was no overall association, but a weak and significant association (OR 1.16) when comparing night-time noise levels >55 dBA in the least socioeconomically deprived areas.…”
Section: Medication Use As An Outcome Variable In Environmental (Noismentioning
confidence: 99%